The Influence of Product Quality, Price Perception, and Promotion on The Purchase Decision of Aqua Brand Drinking Water in The Jakarta Area Final Project - Hashim Alatas; Subur Karyatun; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to analyze the effect of Product Quality, Price Perception, and Promotion on Purchase Decisions in Jakarta. This study uses primary and secondary data with the method of collecting data through questionnaires distributed to 100 respondents. From the results of multiple linear regression analysis shows that Product Quality variable has a positive and insignificant effect, Price Perception has a positive and significant effect, Promotion has a positive and significant effect on Purchase Decisions. Based on the results of this study, it is hoped that people who lived in Jakarta area will be more interested to buying AQUA brand drinking water because of the Product Quality, Price Perception, and Promotion provided by AQUA